Forms Of Recidivist Development In Correctional Institutions - Rasman Habeahan; Rilo Restu Pambudi; Muh. Nasir (Departement of Mathematics Education, 2021)
Training for recidivist prisoners is more focused on independent activities, so it is hoped that recidivists who have already committed crimes will no longer commit crimes and after leaving their sentence will be well received by the outside community. Assimilation is carried out as a further effort in preparation for returning prisoners to social life. The research method used is normative juridical as the main method and empirical juridical as a supporting method, with the nature of analytical descriptive research, then collecting data sourced from secondary data as main data and primary data as supporting data, then the data is processed qualitatively.